2018
DOI: 10.1177/2055668318777989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of waist-worn actigraphy monitors for the assessment of sleep in older adults with and without Alzheimer’s disease

Abstract: Objectives Evaluate differences in sleep characteristics between older adults with and without mild Alzheimer’s disease using waist-worn actigraphy monitors. Methods Actigraph GT3X+ monitors and self-reported sleep and activity logs were used for one week and compared between older adults (N = 85) with (n = 35) and without Alzheimer’s disease (n = 51). Results Participants with Alzheimer’s disease had greater total sleep time and spent more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
2
7
1
Order By: Relevance
“…Self-reported sleep parameters were not associated with actigraphy-measured sleep disruption (Factor 2). These results support the differences between actigraphy-measured and self-reported sleep parameters, which have been reported in studies by DiNapoli et al (2017) and Khou et al (2018). Thus, even among healthy older adults with intact cognitive function and no depression and insomnia, it was not possible to correctly estimate some aging-related sleep characteristics and there was difficulty obtaining correct assessments of these age-related sleep characteristics solely from either actigraphy or self-reported sleep questionnaires.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Self-reported sleep parameters were not associated with actigraphy-measured sleep disruption (Factor 2). These results support the differences between actigraphy-measured and self-reported sleep parameters, which have been reported in studies by DiNapoli et al (2017) and Khou et al (2018). Thus, even among healthy older adults with intact cognitive function and no depression and insomnia, it was not possible to correctly estimate some aging-related sleep characteristics and there was difficulty obtaining correct assessments of these age-related sleep characteristics solely from either actigraphy or self-reported sleep questionnaires.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have found that some factors (i.e., gender [McCrae et al, 2005; Van Den Berg, et al, 2008], insomnia [DiNapoli et al, 2017; Scarlett et al, 2021], cognitive impairment [DiNapoli et al, 2017; Khou et al, 2018], chronic health conditions [McCrae et al, 2005; Scarlett et al, 2021], and depression/depressive symptoms [Scarlett et al, 2021]) can influence the association between actigraphy-measured and self-reported sleep parameters in older adults. Overall, the correlations between actigraphy-measured sleep duration and sleep latency were stronger in older women than those in older men.…”
Section: The Association Between Actigraphy-measured and Self-reporte...mentioning
confidence: 99%
“…The age of the samples ranged from 62.1 [ 61 ] to 86.7 years [ 59 ]. Twenty-six studies included a sample with a diagnosis of AD [ 46 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], and 28 included a sample with a diagnosis of MCI [ 63 , 65 , 66 , 68 , 69 , 84 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ,…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies met the inclusion criteria and used actigraphy to evaluate sleep quality in pathological older people [ 59 , 68 , 82 , 83 , 85 , 101 , 102 , 108 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation